Independent permittivity sensor based on dual T-shaped resonator for solid material characterization - Alam, Syah; Shairi, Noor Azwan; Zakaria, Zahriladha; Alaydrus, Mudrik; Surjati, Indra; Firmansyah, Teguh (2023)
This paper proposes an independent permittivity sensor for solid material characterization. The proposed sensor consists of a dual T-shaped resonator with a single port operating at fr1 = 2.32 GHz as 1st resonator and fr2 = 1.82 GHz as 2nd resonator for direct detection which has independent performance with different sensing hotspot so it can be used independently. The permittivity of the MUT is detected directly by placing the Material Under Test (MUT) above the surface of the 1st and the 2nd resonator. Based on measurement result, the proposed sensor can detect four different MUT independently with different sensing hotspot. This research is very useful for the characterization of solid materials independently for several applications such as biomedical, quality control and pharmaceutical industries.